First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Genetic Features of Tongue Cancer Recurrence in Young Adults - E. S. Kolegova; A. A. Schegoleva; R. S. Vorobev; I. K. Fedorova; D. E. Kulbakin; A. P. Polyakov; A. V. Mordovsky; L. P. Yakovleva; A. S. Vyalov; V. T. Tsiklauri; M. A. Kropotov; N. G. Suchkova; et al. (Bulletin of Experimental Biology and Medicine, 2024)

The Pan-Arctic Continental Slope: Sharp Gradients of Physical Processes Affect Pelagic and Benthic Ecosystems - Bodil A. Bluhm; Markus A. Janout; Seth L. Danielson; Ingrid Ellingsen; Maria Gavrilo; Jacqueline M. Grebmeier; Russell R. Hopcroft; Katrin B. Iken; Randi B. Ingvaldsen; Lis L. Jørgensen; Ksenia N. Kosobokova; Ron Kwok; et al. (Frontiers in Marine Science, 2020)
Continental slopes – steep regions between the shelf break and abyssal ocean – play key roles in the climatology and ecology of the Arctic Ocean. Here, through review and synthesis, we find that the narrow slope regions contribute to ecosystem functioning disproportionately to the size of the habitat area (∼6% of total Arctic Ocean area). Driven by inflows of sub-Arctic waters and steered by topography, boundary currents transport boreal properties and particle loads from the Atlantic and Pacific Oceans along-slope, thus creating both along and cross-slope connectivity gradients in water mass properties and biomass. Drainage of dense, saline shelf water and material within these, and contributions of river and meltwater also shape the characteristics of the slope domain. These and other properties led us to distinguish upper and lower slope domains; the upper slope (shelf break to ∼800 m) is characterized by stronger currents, warmer sub-surface temperatures, and higher biomass across several trophic levels (especially near inflow areas). In contrast, the lower slope has slower-moving currents, is cooler, and exhibits lower vertical carbon flux and biomass. Distinct zonation of zooplankton, benthic and fish communities result from these differences. Slopes display varying levels of system connectivity: (1) along-slope through property and material transport in boundary currents, (2) cross-slope through upwelling of warm and nutrient rich water and down-welling of dense water and organic rich matter, and (3) vertically through shear and mixing. Slope dynamics also generate separating functions through (1) along-slope and across-slope fronts concentrating biological activity, and (2) vertical gradients in the water column and at the seafloor that maintain distinct physical structure and community turnover. At the upper slope, climatic change is manifested in sea-ice retreat, increased heat and mass transport by sub-Arctic inflows, surface warming, and altered vertical stratification, while the lower slope has yet to display evidence of change. Model projections suggest that ongoing physical changes will enhance primary production at the upper slope, with suspected enhancing effects for consumers. We recommend Pan-Arctic monitoring efforts of slopes given that many signals of climate change appear there first and are then transmitted along the slope domain.

Peculiarities of Pharmacokinetics and Bioavailability of Some Cardiovascular Drugs under Conditions of Antiorthostatic Hypokinesia - A. V. Polyakov; A. A. Svistunov; S. N. Kondratenko; I. V. Kovachevich; L. G. Repenkova; M. I. Savelyeva; V. G. Kukes (Bulletin of Experimental Biology and Medicine, 2020)

Prognostic Risk Models for the Development of Cardiovascular Dysfunction in Adolescents with Essential Hypertension - A. S. Kosovtseva; Т. А. Bairova; L. V. Rychkova; V. M. Polyakov; L. I. Kolesnikova (Bulletin of Experimental Biology and Medicine, 2019)

Production and Analysis of Biological Properties of Recombinant Human Apolipoprotein A-I - A. V. Ryabchenko; M. V. Kotova; N. V. Tverdohleb; R. A. Knyazev; L. M. Polyakov (Bulletin of Experimental Biology and Medicine, 2015)

Content of Circulating Extracellular DNA, Plasma Activities of Matrix Metalloproteinases, and Ultrastructure of the Myocardium in Hypothyroid Rats with Hypercholesterolemia - L. M. Polyakov; E. L. Lushnikova; A. A. Karpova; G. S. Russkikh; O. N. Poteryaeva; D. B. Nikityuk; L. M. Nepomnyashchikh; Zh. I. Belonogova; D. V. Sumenkova; R. D. Nepomnyashchikh; V. I. Pichigin (Bulletin of Experimental Biology and Medicine, 2015)

Redox Status as a Metabolic Stage, Integrating Emotional Pattern and Blood Pressure in Adolescents - L. I. Kolesnikova; Zh. V. Prokhorova; B. Ya. Vlasov; V. M. Polyakov (Bulletin of Experimental Biology and Medicine, 2014)

Apolipoprotein A-I as a Carrier of Lipopolysaccharide into Rat Hepatocytes - D. V. Sumenkova; L. M. Polyakov; L. E. Panin (Bulletin of Experimental Biology and Medicine, 2013)

Structural Changes in the Myocardium and Serum Lipid Spectrum in Experimental Hypercholesterolemia and Hypothyroidism - L. M. Nepomnyashchikh; E. L. Lushnikova; L. P. Polyakov; O. P. Molodykh; M. G. Klinnikova; G. S. Russkikh; O. N. Poteryaeva; R. D. Nepomnyashchikh; V. I. Pichigin (Bulletin of Experimental Biology and Medicine, 2013)

Activity of Matrix Metalloproteinases during Antimycobacterial Therapy in Mice with Simulated Tuberculous Inflammation - D. V. Sumenkova; G. S. Russkikh; O. N. Poteryaeva; L. M. Polyakov; L. E. Panin (Bulletin of Experimental Biology and Medicine, 2013)

Plasma Lipoproteins as a Transport Form of Extracellular DNA - D. V. Sumenkova; L. M. Polyakov; L. E. Panin (Bulletin of Experimental Biology and Medicine, 2013)

Effect of Apolipoprotein A-I Complex with Tetrahydrocortisone on Protein Biosynthesis and Glucose Absorption by Rat Hepatocytes - D. V. Sumenkova; R. A. Knyazev; R. S. Guschya; L. M. Polyakov; L. E. Panin (Bulletin of Experimental Biology and Medicine, 2009)

A New Genetic Variant of MDX Mice: Study of the Phenotype - L. I. Krivov; M. A. Stenina; V. N. Yarygin; A. V. Polyakov; V. I. Savchuk; S. A. Obrubov; N. V. Komarova (Bulletin of Experimental Biology and Medicine, 2009)

Effect of Plasma Lipoproteins and Their Complexes with Polysaccharides on Interleukin-1β Concentration in Macrophages of Mice with HA-1 Ascitic Hepatoma - L. M. Polyakov; D. V. Sumenkova; L. E. Panin (Bulletin of Experimental Biology and Medicine, 2009)

Modification and clearance of low density lipoproteins during the formation of endotoxin-lipoprotein complexes - Ya. Sh. Schvartz; L. M. Polyakov; M. I. Dushkin; E. N. Pivovarova (Bulletin of Experimental Biology and Medicine, 2008)

Interaction of apolipoproteins A-I and E in the regulation of DNA, RNA, and protein biosynthesis in cultured rat hepatocytes - L. E. Panin; D. V. Sumenkova; R. A. Knyazev; L. M. Polyakov (Bulletin of Experimental Biology and Medicine, 2007)

Effect of complexes of apolipoprotein A-I with tetrahydrocortisol and pregnenolone on protein biosynthesis in rat hepatocytes culture - L. E. Panin; R. A. Knyazev; D. V. Sumenkova; L. M. Polyakov (Bulletin of Experimental Biology and Medicine, 2007)

Identification of all pachytene bivalents in the common shrew using DAPI-staining of synaptonemal complex spreads - N. M. Belonogova; T. V. Karamysheva; L. S. Biltueva; E. A. Perepelov; J. M. Minina; A. V. Polyakov; N. S. Zhdanova; N. B. Rubtsov; J. B. Searle; P. M. Borodin (Chromosome Research, 2006)

The Use of Homeopathic Preparation Vozraston in the Therapy of Patients with Rheumatoid Arthritis - S. M. Noskov; A. V. Snigireva; L. N. Dolgova; M. A. Somova; D. P. Polyakov (Bulletin of Experimental Biology and Medicine, 2003)

Effects of apolipoproteins C on oxidative phosphorylation in rat liver mitochondria - L. E. Panin; N. I. Shalbueva; L. M. Polyakov (Bulletin of Experimental Biology and Medicine, 2000)

Effects of apolipoproteins C on oxidative phosphorylation in rat liver mitochondria - L. E. Panin; N. I. Shalbueva; L. M. Polyakov (Bulletin of Experimental Biology and Medicine, 2000)

Blood concentration of apolipoproteins A-1, B, and E after intensive physical load and during recovery period - L. E. Panin; O. N. Poteryaeva; N. V. Atuchina; L. M. Polyakov (Bulletin of Experimental Biology and Medicine, 1998)